1995
DOI: 10.2136/sssaj1995.03615995005900010020x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Cadmium Uptake by Hyperaccumulator Thlaspi caerulescens Grown in Nutrient Solution

Abstract: Phytoremediation of heavy‐metal‐contaminated soils can be an inexpensive means to remove hazardous metals from soil. Two metallophytes, Thlaspi caerulescents (J. & C. Presl, a Zn and Cd hyperaccumulator) from Prayon, Belgium, and a Zn‐tolerant ecotype of bladder campion [Silene vulgaris (Moench.) Garcke L.] from Palmerton, PA, were compared with tomato [Lycopersicon lycopersicum (L.) Karsten, metal intolerant] in nutrient solution to characterize Zn and Cd uptake and tolerance. Zinc and Cd were added to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
0
12

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(177 citation statements)
references
References 0 publications
9
156
0
12
Order By: Relevance
“…The results of Zn concentrations in hydroponics are close to those of Shen et al (2000; Zn concentration in solution of 500μM), Zhao et al (1998;1000μM) or Brown et al (1995;3600μM Zn in solution) after approximately 1 month of culture when using the metallicolous PR population. Brown et al (1995) showed values of Zn concentration of 26,000 mg/kg and Zn mass of 35 mg/plant with 3600 μM Zn after 30 days of growth.…”
Section: Comparisons Of Zn Concentration and Mass Between Soils And Hsupporting
confidence: 60%
See 1 more Smart Citation
“…The results of Zn concentrations in hydroponics are close to those of Shen et al (2000; Zn concentration in solution of 500μM), Zhao et al (1998;1000μM) or Brown et al (1995;3600μM Zn in solution) after approximately 1 month of culture when using the metallicolous PR population. Brown et al (1995) showed values of Zn concentration of 26,000 mg/kg and Zn mass of 35 mg/plant with 3600 μM Zn after 30 days of growth.…”
Section: Comparisons Of Zn Concentration and Mass Between Soils And Hsupporting
confidence: 60%
“…Most experiments were performed with nutrient solutions (e.g. Brown et al 1995;Assunção et al 2003a) or with non-contaminated soils supplemented with metal salts (e.g. Meerts et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to that a hyperaccumulator should concentrated more than 10,000 mg kg -1 of Zn or Mn, 1,000 mg kg -1 of Ni, Pb or Cu and more than 100 mg kg -1 of Cd (DW) (Brown et al, 1995). The mustard and amaranth exhibited the highest concentration of metals in shoots, while kenaf was the lowest for all the metals considered and the highest of boron (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Resposta quadrática foi obtida na concentração de Ca nas raízes de E. urophylla, observando-se decréscimo nas doses intermediárias de Zn, enquanto em E. maculata não foi afetada significativamente pelas doses de Zn em solução. Brown et al (1995) também observaram redução na concentração de Ca nas raízes de Thlaspi caerulescens em dose de 3.160 µM de Zn. A concentração de Mg nos tecidos também foi influenciada pelo aumento das doses de Zn em solução.…”
Section: Eucalyptus Maculata Eucalyptus Urophyllaunclassified